ROLE OF BACTERIA AND MICROSCOPIC FUNGI IN AETIOLOGY OF CHRONIC SUPPURATIVE OTITIS MEDIA - L. I. Vasilieva; N. N. Beloglazova; I. E. Bragina; Yu. L. Naboka; V. V. Kiselev (Медицинский вестник Юга России, 2014)
Purpose: To research of spectrum of agents and their biological characteristics in chronic suppurative otitis media (CSOM).Materials and Methods: Вacterial and fungous flora in the middle ear of 102 patients aged from 20 to 70 years with CSOM were studied by microbiological and genetic (PCR) methods. To determine adhesive activity of agents was used rapid method Brilis V.М. and antilysozyme activity – method Bukharin O.V.Results: The majority of cases of CSOM were caused by different species of staphylococci with prevalence S.aureus, S.epidermidis. Mycoplasms, mould and yeast-like fungi took up the second position among the pathogens. Non-clostridial anaerobes and chlamidiae were occurred less frequently. In most cases (>90%) agents of CSOM were possessed of adhesive and antilysozyme activities. Among them more 70% strains had the high and middle level of expression of these signs.Summary: Traditional microbiological method of diagnostics is not an informative, because it leave out of account the role mycoplasms, chlamidiae and non-clostridial anaerobes in forming of disease. Main strains of agents of CSOM are possessed of significant adhesive and antilysozyme activities. These signs influence on gravity and duration of course of disease.